2019
DOI: 10.24925/turjaf.v7i6.866-870.2438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracts of Feed Additives Including Rosemary (Rosmarinus officinalis) and Aloe Vera (Aloe barbadensis) on the Growth Performance and Feed Utility of Nile Tilapia (Oreochromis niloticus)

Abstract: This study was performed to determine the effects of the extracts of two alternative antimicrobial agents that do not harm the ecosystem (rosemary, Rosmarinus officinalis and aloe vera, Aloe barbadensis) when added to the feed of tilapia (Oreochromis niloticus) on the growth performance, proximate composition, and biometric characteristics. Rosemary extract was added to the experimental diet in ratios of 0.1%, 0.25%, and 0.5% while aloe vera extract was added to the experimental diet in ratios of 0.5%, 1%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In this research, the condition factor increased in the groups fed with cypermethrin, while it decreased in those fed with a black cumin oil diet. Yılmaz et al (2019), investigated the effects of rosemary and aloe vera extract on growth performance and feed utilization of Nile tilapia ( O. niloticus ) and concluded that plant extracts decreased the condition factor. In another study, it was reported that the condition factor decreased when green tea by‐product and 2% black cumin were used, similar to this study (Cho et al, 2007; Diab et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, the condition factor increased in the groups fed with cypermethrin, while it decreased in those fed with a black cumin oil diet. Yılmaz et al (2019), investigated the effects of rosemary and aloe vera extract on growth performance and feed utilization of Nile tilapia ( O. niloticus ) and concluded that plant extracts decreased the condition factor. In another study, it was reported that the condition factor decreased when green tea by‐product and 2% black cumin were used, similar to this study (Cho et al, 2007; Diab et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HSI is an index measured by calculating the ratio between the liver and body weight of fish. Regardless of the size of the fish, enlarged livers can be seen in fish, and one of the most important reasons for this situation is that there is too much fat in the ration, which is stored in the liver (Storebakken & Austreng, 1987; Yılmaz et al, 2019). In this study, the highest HSI index value was calculated in the fish in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, the growth‐promoting effects of other medicinal plants have also been confirmed in gilthead seabream fed by Salvia officinalis and Lippia citriodora leaf extracts (Salomón et al, 2020), and in common carp fed by dietary ginger powder (Fazelan et al, 2020) or rosemary leaf powder (Yousefi et al, 2019) and in rainbow trout fed by curcuma longa (Yonar et al, 2019). Whilst, no marked effects on growth performance and feed utilization were observed in Nile tilapia fed by gotu kola powder ( Centella asiatica ) (Srichaiyo et al, 2020), in rainbow trout fed by lemon verbena leaf powder (Hoseinifar, Shakouri, et al, 2020), in Nile tilapia fed Rosmarinus officinalis and Aloe barbadensis extracts (Yılmaz et al, 2019), and in common carp fed oak leaf extract (Paray et al, 2020). These contradictory results revealed that the effects of plant‐derived products are species‐specific and may be related to herbal species, supplementation dose, experimental condition as well as fish species (Hoseinifar, Shakouri, et al, 2020; Reverter et al, 2016; Tan et al, 2018; Zakęś et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Yilmaz et al (2019) detected no remarkable change in the growth performance of Oreochromis niloticus that were fed by diets with different amounts of rosemary extract. The reason for different results obtained in different studies on fish growth performance can be associated with fish species, various doses of herbal extract, various intestinal microbiota and trial conditions.…”
mentioning
confidence: 85%
“…The results of our study revealed that feeding on a diet containing rosemary extract did not affect body composition (protein, lipid, ash and moisture) in C. carpio. Similarly,Hassan et al (2018) andYilmaz et al (2019) stated no significant difference in body composition of O. niloticus fed with a diet containing rosemary extracts compared with the control group.…”
mentioning
confidence: 90%